The Occurrence of Recent-Subrecent Seabed Acoustic Anomalies and Its Relationship with Structural Uplift around the Waipoga Trough, West Papua-Indonesia - Dida Kusnida; Ali Albab; Tumpal B. Nainggolan; Yulinar Firdaus (Indonesian Journal on Geoscience, 2023)
Marine Geological Institute acquired high-resolution seismic and acoustic data during a survey in the Waipoga Trough-West Papua in 2018. The profiles show acoustically blanking, turbid, and cloudy occur along the trough floor over 3,000 km2. Many accoustic chimneys are breaking through the seabed of recent and subrecent sediment layers. It is suggested due to the local expulsion of methane gas. The pockmarks occur as transparent and turbid acoustic characteristics. They locally have relief down to 2-10 m below the seafloor with horizontal dimensions up to 25 -100 m in width. Methane formation due to the rapid deposition of organic-rich sediment down the uplifted area around the trough, associated with thrust fold tectonics is suggested as a triggering agent for the acoustic anomaly formation.